(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
This article analyzes the characteristics and the purposes that the object “photography” has in Proust’s Recherche and in Roland Barthes’ La chambre claire, by recognizing within these two texts a the double challenge represented by photography itself: that of being a transparent object and that of allowing the fruition of the extra-temporality. Barthes’ realism, however, prevents the critic from considering in its full extent the cognitive value of photography, as configured in Proust’s text, which is placed in watermark in relation to the Barthes’ discourse. Proust’s complex position with respect to the object “photography”, which he criticizes, among many other reasons, for thesnap-shot platitude, includes even a possible parallelism with the involuntary memory, since the heuristic meaning of photography is connected to the cognitive and affective dinamycs which guide our processes of remembrance and creative relationship with our own past.